Cross-talk-free, high extinction ratio, and ultra-compact all‑optical 4 × 2 encoder using graphene-based plasmonic waveguides - Saima Kanwal; Mohammed R. Saeed; Faris K. AL-Shammri; Mir Hamid Rezaei (Scientific Reports)
Abstract This paper presents an all-optical 4 × 2 encoder based on graphene-plasmonic waveguides for operation in the wavelength range of 8–12 μm. The basic plasmonic waveguide consists of a silicon (Si) strip and a graphene sheet supported by two dielectric ridges. Surface plasmon polaritons (SPPs) are stimulated in the spatial gap between the graphene sheet and the Si strip. The effect of geometric parameters and chemical potential of the graphene sheet changes on the suggested waveguide’s waveguiding behavior is meticulously investigated using the three-dimensional finite-difference time-domain (3D-FDTD) method. The encoder comprises a straight waveguide to detect the state of the In0 input and two Y-combiners with outputs Out0 and Out1 to detect the state of the In1, In2, and In3 inputs. The encoder exhibits a minimum extinction ratio (ER min ) of 19 dB at a wavelength of 10 μm. In addition, the cross-talk (CT) and insertion loss (IL) values are −21.3 and −1.31 dB, respectively. The encoder offers an ultra-compact structure with a total footprint of 4.25 μm2. Due to its exceptional waveguiding features, low CT and IL values, and high ER min , the proposed encoder holds promise for various communication and signal processing applications.